NEW SIRENIAN RECORD FROM LOWER PLIOCENE SEDIMENTS OF TUSCANY (ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
A left humerus of a sirenian found in the upper part of a marine succession from Camigliano (Siena, Italy) is described. Foraminiferal assemblages reveal that this humerus belongs to a specimen living during the early Zanclean (Globorotalia margaritae Zone) in a shallow marine environment and that was probably subjected to post-mortem transport to a shelf environment under storm wave action. This new Tuscan record can be ascribed, for size and stratigraphic position, to Metaxytherium cf. subapenninum. The dimensional comparison of this humerus with those of its supposed ancestor M. serresii confirms the remarkable increase in body size of M. subapenninum compared with the former M. serresii.
Keywords: Sirenia; Metaxytherium; Foraminifers; Pliocene; Tuscany; Italy